Rozwiąż równania:


a) 5x + 13 = 3x - 7 b) 3(x - 1) + 2 = 8



c) 4x - 4 + 2x = 4 - 7x + 31 d) 4(x – 1) = 6(1 + x)

e)
r5 -3 = x + 1/5


Odpowiedź :

Odpowiedź:

a) 5x + 13 = 3x - 7

2x=-7-13

2x=-20

x=-10

b) 3(x - 1) + 2 = 8

3x-3+2=8

3x=8-2+3

3x=9

x=3

c) 4x - 4 + 2x = 4 - 7x + 31

4+2x+7x=31+4+4

13x=39

x=3

d) 4(x – 1) = 6(1 + x)

4x-4=6+6x

4x-6x=6+4

-2x=10

x=-5

e)

r5 -3 = x + 1/5 (rozumiem, ze te r przed 5 to niechcaco?)

5-3=x+1/5  mnozymy *5

25-15=5x+1

-5x=1+15-25

-5x=-9

x=9/5=1 4/5

Szczegółowe wyjaśnienie:

mam nadzieję ze pomogłam.licze na naj